In Vitro Penetration of Curcumin Self-Nanoemulsifying Drug Delivery System (SNEDDS) in Transdermal Gel Formulations - Sandi Cahya Prawira; Zainur Rahman Hakim (Faculty of Pharmacy Universitas Pancasila, 2026)
Curcumin is a natural bioactive compound with potent antibacterial properties; however, its clinical utility is restricted by poor aqueous solubility (BCS Class II) and low systemic bioavailability. This study aimed to overcome these barriers by formulating curcumin into a self-nanoemulsifying drug delivery system (SNEDDS) incorporated into a transdermal gel. Optimization involved a synergistic blend of virgin coconut oil (VCO), Tween 80, and Cremophor RH 40, which spontaneously forms a nanoemulsion upon aqueous contact. The optimized formulation yielded nanoparticles with a size of 257.9 nm, a polydispersity index (PDI) of 0.018, and a zeta potential of − 29 mV. In vitro penetration tests using a Franz diffusion cell with guinea pig skin revealed a significant improvement (p < 0.05) in drug delivery. The curcumin SNEDDS gel achieved a cumulative permeation of 187.53 ± 16.27 μg/cm², significantly outperforming the conventional curcumin gel (125.19 ± 8.41 μg/cm²). These findings demonstrate that the SNEDDS based transdermal approach is a highly effective strategy for enhancing skin penetration and the therapeutic potential of curcumin.